The Old Wine in the New Skin: Integrating Acholi Ritual Pots in Contemporary space - Adong, Sanday R.; Mutungi, Emmanuel (Machakos University, 2018)
The purpose of the study is to design and produce pots derived from indigenous Acholi ritual pots for contemporary space and their resultant effect in promoting sustainable development that is prosociety. Specifically the study analyzes how Acholi ritual pots can be used in contemporary space, design pots for specific contemporary spaces inspired by the ritual pots, and produce pottery ware suitable for contemporary spaces. Guided by the componential theory of creativity by Teresa Amabile (1983), the study is qualitative and employs ethnographic research technique in collecting data from four potters in Atanga Sub-county in Pader district and Boma Hotel in Gulu district both in Northern Uganda. Using participant observation, interviews and photography, data was collected and thematically analyzed through studio experimentationto come up with designs that resulted into functional pottery for using at Boma hotel in Gulu town. The conclusion reveals that indigenous ritual pots can be redesigned to fit in the contemporary spaces and community accepts them. The study recommends that indigenous pots need to be redesigned for contemporary spaces such that negative perception that they are archaic could be mitigated. Key words: Acholi ritual pots, contemporary space, pottery, sustainable development
Keywords: Acholi ritual pots